2021
DOI: 10.1177/1358863x211008249
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus was not associated with lower amputation-free survival after open revascularization for chronic limb-threatening ischemia – A nationwide propensity score adjusted analysis

Abstract: The risk of major amputation is higher after urgently planned endovascular therapy for chronic limb-threatening ischemia (CLTI) in patients with diabetes mellitus (DM). The aim of this nationwide cohort study was to compare outcomes between patients with and without DM following urgently planned open revascularization for CLTI from 2010 to 2014. Out of 1537 individuals registered in the Swedish Vascular Registry, 569 were registered in the National Diabetes Register. A propensity score adjusted Cox regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…DM was the only factor among several that influenced patient survival and limb preservation and did not have a measurable effect on graft patency. Finally, Lilja et al [5] found no differences in mortality, cardiovascular death or major amputations between DM and non-DM in 1537 urgently planned open revascularisations for CLTI, including 569 DM. However, DM had significantly higher rates of stroke and myocardial infarction.…”
Section: Introductionmentioning
confidence: 97%
“…DM was the only factor among several that influenced patient survival and limb preservation and did not have a measurable effect on graft patency. Finally, Lilja et al [5] found no differences in mortality, cardiovascular death or major amputations between DM and non-DM in 1537 urgently planned open revascularisations for CLTI, including 569 DM. However, DM had significantly higher rates of stroke and myocardial infarction.…”
Section: Introductionmentioning
confidence: 97%